A Dielectric-Loaded FSS-Based Radome Design With an Adjustable RCS Reduction Band - Yuan-Chang Hou; Sang-Fei Wang; Wen-Jiao Liao (IEEE Access)
This paper presents a hybrid radome panel that features a controllable radar cross section (RCS) reduction band. To achieve RCS suppression, the structure combines periodic frequency selective surfaces (FSSs) and dielectric loadings of different compositions, which leads to wave cancellation due to propagation delays of opposite phases. By modifying the thickness of the radome and the relative permittivity ratio, the RCS reduction band can be adjusted and optimized to obtain a wider reduction bandwidth. Furthermore, the evaluation method implemented in this work, that is, summing up the reflectivity of each radome segment, can rapidly assess the radome’s RCS reduction performance. Simulation and measurement results of the 75 mm $× 150$ mm radome panel are in good agreement. They validate that the panel provides substantial RCS reduction in X- and Ku-bands, while the C-band antenna operation is unperturbed.